Penerapan Model Pembelajaran Matematika Realistik (PMR) Pada Materi Perkalian Untuk meningkatkan Hasil Belajar Matematika Kelas II Sekolah Dasar Negeri 005 Sungai Bungo - Handayani, Fitri; Rahmadani, Nia; Simbolon, Parlindungan; Nikmah, Nikmah; Maspuri, Maspuri (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2023)
This classroom action research purpose is to improve the students’ ability to calculate multiplication at second grade of SDN 005 Sungai Bungo, Kampar Kiri Hilir District, Kampar Regency in the 2022/2023 academic year through Realistic Mathematical Approach. The form research is classroom action research consisting of two cycles, each cycle consisting of four stages: planning, implementing, observing and reflecting. The research subjects were 26 second grade students of SDN 005 Sungai Bungo. Data collection techniques were observation and tests. The data analysis technique used an interactive model analysis technique which consists of three components of analysis; data reduction, data presentation, and drawing conclusions or verification. The results of this study were (1) there is an increase in the average score obtained by students from the previous initial test of 58.46; then in the first cycle test from 74.03 to 83.46 in the second cycle, (2) there is an increase in the percentage of student learning completeness which was only 38.46% in the initial test; and in the first cycle test 84.61%; then in the second cycle to 100%. The results of the research show that using a realistic mathematical approach improve the ability to calculate multiplication in second grade students of SDN 005 Sungai Bungo, Kampar Kiri Hilir District, Kampar Regency in the 2022/2023 academic year